Dispersions of (meth) acrylate copolymers and their use as binders for cementitious materials
By using specific composition (meth)acrylate copolymers and free radical-induced emulsion polymerization techniques, dispersions with low ammonia aldehyde release and optimized mechanical properties in cementitious materials were prepared, and ammonia aldehyde in the prior art was solved. Problems of pollution and insufficient mechanical properties.
Patent Information
- Application Number
- CN202380038285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-05
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-10
AI Technical Summary
Existing acrylate copolymer dispersions release ammonia and aldehydes during cement hydration, resulting in environmental contamination, and mechanical properties such as tensile strength and bond strength are not adequately optimized, and methods for improving performance usually lead to other aspects. Performance deterioration.
The dispersion is prepared by radical-induced emulsion polymerization technology to control the glass by using a (meth)acrylate copolymer composed of monoethylenically hard monomers, soft monomers, specific hydroxyalkyl monomers and unsaturated monomers. The transformation temperature (Tg) is in the range of -30°C to 10°C, optimizing the mechanical properties of the dispersion and low ammonia aldehyde emission.
Low ammonia aldehyde release and good mechanical properties in cemented materials are achieved, and the tensile strength and bonding strength of the dispersion are improved, while avoiding other deterioration of performance.
Smart Images

Figure BDA0005116999980000096 
Figure BDA0005116999980000151 
Figure BDA0005116999980000161
Abstract
Description
Technical Field
[0001] The present invention relates to a dispersion of a (meth)acrylate copolymer polymerized with hydroxyalkyl (meth)acrylate comonomer units and to its use in cementitious materials. Background Art
[0002] Flexible polymer modified cementitious materials are widely used in apartments, basements, underground water tanks, etc. due to their good tensile strength, adhesion, flexibility, impermeability, corrosion resistance, crack resistance, durability, etc. Polymer dispersions are generally used as modifiers in flexible polymer modified cementitious waterproof materials. In practice, polymer dispersions of acrylate copolymers and ethylene-vinyl acetate copolymers are conventionally used, among which dispersions of acrylate copolymers containing (meth)acrylamide comonomers are most widely used due to good processability and characteristics of modified cementitious waterproof materials.
[0003] CN 102911580 A discloses a cross-linked acrylic dispersion for waterproof coatings, which has a high cross-linking density, excellent adhesion to cementitious substrates, strong adhesion, coating strength and excellent cement retarding ability. The dispersion can be applied to both single-component and two-component waterproof coatings. The dispersion is prepared from deionized water, an initiator, an emulsifier, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, diacetone acrylamide, adipic acid dihydrazide, a defoamer and a neutralizer.
[0004] CN 101891859 A discloses an elastic styrene-acrylic dispersion for polymer cement waterproof coating, which provides the produced coating film with improved toughness, strength and waterproof properties. The dispersion is prepared from fatty alcohol polyoxyethylene ether sulfate, fatty alcohol polyoxyethylene ether (meth) acrylate, n-butyl acrylate, styrene, AMPS and N-hydroxymethyl acrylamide.
[0005] WO 2016001256 A1 discloses a dispersion of a (meth)acrylate copolymer containing hydroxyalkyl (meth)acrylate comonomer units, the dispersion being obtained by polymerization of monomers comprising: (a) 25% to 45% by weight of at least one monovinyl aromatic monomer and / or methyl methacrylate, based on the total monomer weight; (b) 50% to 70% by weight of at least one (meth)acrylate C 4-8 (c) 2 to 7% by weight of at least one hydroxyalkyl (meth)acrylate; (d) 0 to 1% by weight of at least one α,β-monoethylenically unsaturated C 3-6Monocarboxylic acid or dicarboxylic acid; and (e) 0 to 0.65% by weight of (meth)acrylamide, N-hydroxyalkyl (meth)acrylamide, and / or 2-acrylamido-2-methylpropane sulfonic acid; and use of the dispersion for flexible cementitious waterproofing materials.
[0006] Such dispersions have many disadvantages. One disadvantage is that ammonia is released into the environment due to hydrolysis under strong alkaline conditions produced by cement hydration when the acrylamide group is mixed with cement. Ammonia is an irritant and may cause burns to the skin, eyes, mouth and lungs. Another disadvantage is that aldehydes are released into the environment. And aldehydes may pose an even greater threat to human health. The third disadvantage is that mechanical properties (such as tensile strength, elongation and bond strength) are not optimized. Last but not least, many methods have been taken to improve the performance of dispersion polymers, which usually make performance improvements in some aspects at the cost of performance degradation in some other aspects.
[0007] It would be advantageous to provide a polymer dispersion useful in cementitious materials which has low ammonia and aldehyde emissions and good mechanical properties. Summary of the invention
[0008] One aspect of the present invention relates to a dispersion of a (meth)acrylate copolymer obtained by polymerization of monomers comprising: based on the total monomer weight,
[0009] (a) 10 to 45% by weight of at least one monoethylenic hard monomer;
[0010] (b) 54 to 89% by weight of at least one monoethylenically soft monomer;
[0011] (c) 0.5 to 5.0% by weight of at least one monomer represented by formula (1)
[0012] CH2=C(R 1 )CONR 2 R 3 Formula (1)
[0013] Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and
[0014] (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
[0015] Another aspect of the present invention is to provide use of the above dispersion polymer as a cementitious material. DETAILED DESCRIPTION
[0016] Unless otherwise defined, all terms / terminology / nomenclature used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0017] The expressions "a," "an," and "the" when used to qualify a term include both the plural and singular forms of the term.
[0018] As used herein, the term "polymer" or "polymers" includes both homopolymers (ie, polymers prepared from a single reactive compound) and copolymers (ie, polymers prepared by the reaction of at least two reactive monomeric compounds to form the polymer).
[0019] The name (meth)acrylate and similar names are used herein as a shorthand notation for "acrylate and / or methacrylate".
[0020] As used herein, the name (meth)acrylate copolymer and similar names refer to copolymers prepared by the reaction of monoethylenic monomers including, but not limited to, (meth)acrylate monomers, monovinyl aromatic monomers, and the like, and other reactive monomers.
[0021] Unless otherwise indicated, all percentages and ratios are expressed by weight.
[0022] Within the context of the present application, the term Fox Tg refers to the glass transition temperature Tg as calculated according to the Fox equation as disclosed in TGFox, Bulletin of the American Physical Society, Vol. 1, No. 3, p. 123 (1956):
[0023] 1 / Tg=W1 / Tg1+W2 / Tg2+···+W n / Tg n
[0024] in
[0025] W1, W2, ...W n are the mass fractions of monomers 1, 2, ... n, respectively, and
[0026] Tg1, Tg2, ... Tg n are the glass transition temperatures of the homopolymers of monomers 1, 2, ...n, respectively, in degrees Kelvin.
[0027] The Tg values for homopolymers of most monomers are known and are listed, for example, in Ullmann's Ecyclopedia of Industrial Chemistry, Vol. 5, A21, p. 169, VCH Publishers, Weinheim, 1992. Other sources of glass transition temperatures for homopolymers include, for example, J. Brandrup, EH Immergut, Polymer Handbook, 1st ed., John Wiley, New York 1966, 2nd ed., John Wiley, New York 1975, and 3rd ed., John Wiley, New York 1989.
[0028] In the present invention, a monoethylenic monomer is considered a hard monomer if it can produce a homopolymer with a calculated Fox Tg exceeding 10°C, otherwise it will be considered a soft monomer.
[0029] The dispersion of the (meth)acrylate copolymer is obtained by polymerization of monomers comprising: based on the total monomer weight,
[0030] (a) 10 to 45% by weight of at least one monoethylenic hard monomer;
[0031] (b) 54 to 89% by weight of at least one monoethylenically soft monomer;
[0032] (c) 0.5 to 5.0% by weight of at least one monomer represented by formula (1)
[0033] CH2=C(R 1 )CONR 2 R 3 Formula (1)
[0034] Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and
[0035] (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
[0036] The at least one monoethylenic hard monomer (a) may include, but is not limited to, methyl methacrylate, tert-butyl acrylate, benzyl methacrylate, ethyl methacrylate, vinyl maleate, vinyl acetate, vinyl butyrate, vinyl formate, vinyl valerate, vinyl versatate, monovinyl aromatic monomers, and any combination thereof. The monovinyl aromatic monomer is selected from the group consisting of styrene, α-methylstyrene, o- or p-vinyltoluene, p-bromostyrene, p-tert-butylstyrene, o-, m- or p-chlorostyrene, and any combination thereof.
[0037] In a preferred embodiment, the at least one monoethylenic hard monomer (a) is selected from methyl methacrylate and styrene. In a more preferred embodiment, the at least one monoethylenic hard monomer (a) is styrene.
[0038] The monomer (a) is preferably used in an amount of 15% to 45%, more preferably 20% to 40%, most preferably 20% to 30%, based on the total weight of all monomers. The at least one monovinyl aromatic monomer and the methyl methacrylate monomer, if both are used, may be used in any ratio.
[0039] The at least one monoethylenic soft monomer (b) may include, but is not limited to, methyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, nonyl acrylate, ethyl acrylate, decyl methacrylate, isodecyl methacrylate, hexyl (meth)acrylate, cyclohexyl acrylate, dodecyl (meth)acrylate, octyl methacrylate, propyl acrylate, ethylene adipate, diethyl fumarate, 1,4-butadiene, 1-pentene, di-2-ethylhexyl maleate, di-2-ethylhexyl fumarate, and mixtures thereof.
[0040] In a preferred embodiment, an alkyl acrylate having 4 to 12 carbon atoms in the alkyl group, such as n-butyl acrylate and 2-ethylhexyl acrylate, is used as the soft monomer.
[0041] The at least one monoethylenically soft monomer (b) is preferably used in an amount of 54 to 84%, more preferably 59 to 79%, most preferably 69 to 79%, based on the total weight of all monomers.
[0042] The monomer (c) represented by the formula (1) may have: 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl containing 2 to 8 carbon atoms. Preferably, R 2 is a hydroxyalkyl group containing 2 to 6 carbon atoms, and R 3 is H, C1-C6 alkyl or hydroxyalkyl containing 2 to 6 carbon atoms. More preferably, R 2is a hydroxyalkyl group containing 2 to 4 carbon atoms, and R 3 It is H, C1-C4 alkyl or hydroxyalkyl having 2 to 4 carbon atoms.
[0043] More specifically, the hydroxyalkyl group may be selected from, but is not limited to, hydroxyethyl, hydroxypropyl, hydroxybutyl, hydroxypentyl, hydroxyhexyl, hydroxyheptyl, and hydroxyoctyl. More specifically, monomer (c) may be selected from, but is not limited to, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxyethyl)methacrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxypropyl)methacrylamide, N-(1-hydroxypropyl)acrylamide, N-(1-hydroxypropyl)methacrylamide, N-(3-hydroxypropyl)acrylamide, N-(3-hydroxypropyl)methacrylamide, N-(2-hydroxybutyl)acrylamide, N-(2-hydroxybutyl)methacrylamide, N-(3-hydroxybutyl)acrylamide, N-(3-hydroxybutyl)methacrylamide, N-(4-hydroxybutyl)acrylamide, N-(4-hydroxybutyl)methacrylamide, N,N-bis(2-hydroxyethyl)acrylamide In a preferred embodiment, monomer (c) is selected from N-(2-hydroxyethyl) acrylamide and N,N-bis(2-hydroxypropyl) methacrylamide.
[0044] Monomer (c) may be used in an amount of 0.5 to 4%, preferably 0.8 to 3%, more preferably 0.8 to 2.2%, most preferably 1 to 2%, based on the total weight of all monomers.
[0045] The monomer (d) (i.e., the hydrophilic monoethylenically unsaturated monomer) may include, but is not limited to, monoethylenically unsaturated carboxylic acids, such as (meth)acrylic acid, itaconic acid, fumaric acid, citraconic acid, sorbic acid, cinnamic acid, glutaconic acid and maleic acid; monoethylenically unsaturated carboxylic acid anhydrides, such as itaconic anhydride, fumaric anhydride, citraconic anhydride, sorbic anhydride, cinnamic anhydride, glutaconic anhydride and maleic anhydride; and hydroxyalkyl esters of monoethylenically unsaturated carboxylic acids, such as hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate.
[0046] The monomer (d), if present, is preferably used in an amount of from 0.5% to 25%, preferably from 1% to 15%, more preferably from 1.5% to 10%, based on the total weight of all monomers.
[0047] Many other monoethylenically unsaturated monomers may be used in the present invention. Such monomers may include, but are not limited to, vinyl alkanoate monomers and monoethylenically unsaturated dicarboxylic acid esters and tricarboxylic acid ester monomers. Vinyl alkanoate monomers may include C2-C 11 The monoethylenically unsaturated dicarboxylic acid ester and tricarboxylic acid ester monomer can include but is not limited to diethyl maleate, dimethyl fumarate, ethyl methyl itaconate, dihexyl succinate, didecyl succinate or any mixture thereof.
[0048] Monomer used for the present invention can further comprise one or more crosslinking monomers.Crosslinking monomers can be selected from di- or polyisocyanates, polyaziridines, polycarbodiimide, polyoxazoline, glyoxal, triol, epoxy molecule, organosilane, carbamate, diamines and triamines, hydrazides, carbodiimide and polyethylenically unsaturated monomers. In the present invention, suitable crosslinking monomers include, but are not limited to, glycidyl (meth)acrylate; N-hydroxymethyl (meth)acrylamide; (isobutoxymethyl)acrylamide; vinyltrialkoxysilanes such as vinyltrimethoxysilane; alkylvinyldialkoxysilanes such as dimethoxymethylvinylsilane; (meth)acryloxyalkyltrialkoxysilanes such as (meth)acryloxyethyltrimethoxysilane, (3-acryloxypropyl)trimethoxysilane and (3-methacryloxypropyl)trimethoxysilane; allyl methacrylate; diallyl phthalate; 1,4-butylene glycol dimethacrylate; 1,2-ethylene glycol dimethacrylate; 1,6-hexanediol diacrylate; divinylbenzene or any mixture thereof.
[0049] It should be understood that the total percentage of all monomers is 100% by weight.
[0050] In a preferred embodiment, the dispersion of the (meth)acrylate copolymer is obtained by polymerization of monomers comprising: based on the total monomer weight,
[0051] (a) 15 to 45% by weight of at least one monoethylenic hard monomer;
[0052] (b) 54 to 84% by weight of at least one monoethylenically soft monomer;
[0053] (c) 0.5 to 4% by weight of at least one monomer represented by formula (1)
[0054] CH2=C(R 1 )CONR 2 R 3 Formula (1)
[0055] Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and
[0056] (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
[0057] In a more preferred embodiment, the dispersion of the (meth)acrylate copolymer is obtained by polymerization of monomers comprising: based on the total monomer weight,
[0058] (a) 20 to 40% by weight of at least one monoethylenic hard monomer;
[0059] (b) 59 to 79% by weight of at least one monoethylenically soft monomer;
[0060] (c) 0.8% to 2.2% by weight of at least one monomer represented by formula (1)
[0061] CH2=C(R 1 )CONR 2 R 3 Formula (1)
[0062] Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and
[0063] (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
[0064] In a most preferred embodiment, the dispersion of the (meth)acrylate copolymer is obtained by polymerization of monomers comprising: based on the total monomer weight,
[0065] (a) 20 to 30% by weight of at least one monoethylenic hard monomer;
[0066] (b) 69 to 79% by weight of at least one monoethylenically soft monomer;
[0067] (c) 1 to 2% by weight of at least one monomer represented by formula (1)
[0068] CH2=C(R 1 )CONR 2 R 3 Formula (1)
[0069] Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and
[0070] (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
[0071] In one embodiment of the present disclosure, the (meth)acrylate copolymer according to the present disclosure may have a Tg in the range of -30°C to 10°C, preferably in the range of -20°C to 10°C, more preferably in the range of -10°C to 0°C. Tg may affect tensile strength and adhesive strength.
[0072] The free radical initiated emulsion polymerization can be carried out in the presence of an exogenous polymer seed in an amount of 0.04% to 1.5% by weight based on the total weight of all monomers. An exogenous polymer seed is a polymer seed prepared in a separate reaction step or a commercially available polymer seed, the monomer composition of which is different from the monomer composition of the polymer prepared by the free radical initiated emulsion polymerization. The preparation of exogenous polymer seeds is familiar to the technician and is typically completed by introducing a relatively small amount of monomer and a relatively large amount of emulsifier as an initial charge into a reaction vessel and by adding a sufficient amount of polymerization initiator at the reaction temperature. Polystyrene or polymethyl methacrylate polymer seeds are particularly preferred. Before initiating the polymerization reaction, the entire amount of exogenous polymer seeds is introduced into the polymerization vessel as an initial charge. The entire amount of monomers (a) to (d) can be continuously charged into the polymerization vessel in the form of a monomer emulsion under polymerization conditions. Particularly useful are those whose particles have a narrow particle size distribution and a weight average diameter D of less than 100 nm, typically about 5 nm to about 50 nm, and typically about 15 nm to 35 nm. w of polymer seeds.
[0073] Free radical initiated emulsion polymerization is carried out in the presence of an emulsifier, an initiator and optionally a free radical chain transfer agent and other additives, which are those conventionally used in the art.
[0074] Suitable emulsifiers for preparing the dispersion of the (meth) acrylate copolymer according to the present invention include nonionic emulsifiers, anionic emulsifiers, or combinations thereof, preferably anionic emulsifiers. The emulsifier can be used in an amount of 0.1% to 3% by weight based on the total weight of all monomers. The emulsifier can be introduced in the form of a monomer emulsion. It is also possible to introduce a portion of the emulsifier as an initial charge into the polymerization vessel before initiating the polymerization reaction, and to add the remaining amount of the emulsifier in the form of a monomer emulsion under polymerization conditions.
[0075] Examples of conventional nonionic emulsifiers include ethoxylated mono-, di- and tri-alkylphenols (EO degree: 3 to 50, alkyl group: C4 to C 12 ) and also ethoxylated fatty alcohols (EO degree: 3 to 80; alkyl group: C6 to C 36 ), where EO degree means the degree of ethoxylation. An example is Lutensol Grade (C 12 To C 14 , fatty alcohol ethoxylate, EO degree: 3 to 8), Lutensol Grade (C 13 C 15 Oxidation alcohol ethoxylate, EO degree: 3 to 30), Lutensol Grade (C 16 C 18 , fatty alcohol ethoxylate, EO degree: 11 to 80), Emulan Grade (C 13 Oxidation alcohol ethoxylates, EO degree: 20 to 40), and Lutensol Grade (C 13 Oxidized alcohol ethoxylates, EO degree: 3 to 20), all commercially available from BASF SE.
[0076] Examples of conventional anionic emulsifiers include alkali metal and ammonium salts of: alkyl sulfates (alkyl: C5 to C 12 ), with ethoxylated alkanol (EO degree: 2 to 30, alkyl: C 12 To C 18 ) and having ethoxylated alkylphenol (EO degree: 3 to 50, alkyl group: C4 to C 12 ) sulfuric acid monoesters, alkyl sulfonic acids (alkyl: C 12 To C 18 ), and alkyl aryl sulfonic acid (alkyl group: C9 to Ci8).
[0077]
[0078] As suitable anionic emulsifiers, mention may also be made of compounds of the general formula (I).
[0079] Where R 1 and R 2 independently H or C 4-24 Alkyl, preferably straight chain or branched C 6-18 Alkyl, especially C6, C 12 or C 16 alkyl, and not H, and M 1 and M 2 It may be an alkali metal ion and / or an ammonium ion, preferably sodium, potassium or ammonium, with sodium being particularly preferred. Compound (I) is known from, for example, US Pat. No. 4,269,749 and is commercially available.
[0080] Technical mixtures containing fractions of 50 to 90% by weight of monoalkylated products are commonly used, such as 2A1 (commercially available from The Dow Chemical Company).
[0081] Suitable initiators for preparing dispersions of (meth)acrylate copolymers according to the present invention are free radical water-soluble substances, in particular water-soluble peroxides or persulfates, such as hydrogen peroxide, potassium persulfate, sodium persulfate and ammonium persulfate, tert-butyl hydroperoxide, peracetic acid, etc. It is also possible to use a redox catalyst consisting of the above types of peroxides or persulfates and a reducing agent commonly used for this purpose (such as ascorbic acid, sodium bisulfite, sodium bisulphite, etc.). Two or more initiators can be used in the emulsion polymerization. Typically, the initiator can be used in an amount of 0.1% to 3%, preferably 0.1% to 2%, by weight based on the total weight of all monomers. The initiator can be introduced into the polymerization vessel as an initial charge before initiating the polymerization. It is also possible to introduce a portion of the initiator into the polymerization vessel as an initial charge before initiating the polymerization and to add the remaining amount continuously under polymerization conditions.
[0082] In order to reduce residual monomers, it is common to add further initiators after the substantial end of the emulsion polymerization, ie after a monomer conversion of at least 95%.
[0083] In addition to the above components, free radical chain transfer agents can also be used to control the molecular weight of the copolymer obtained by polymerization. The amount of chain transfer agent is generally less than 5% by weight, preferably less than 1% by weight, based on the total weight of all monomers. In particular, organic mercaptan compounds are suitable as chain transfer agents, such as tert-dodecyl mercaptan.
[0084] The free radical initiated emulsion polymerization is carried out at a temperature ranging from 50°C to 120°C, preferably 70°C to 95°C.
[0085] The dispersion of the (meth)acrylate copolymer containing hydroxyalkyl (meth)acrylate comonomer units according to the present disclosure may also contain conventional additives known in the art, such as antimicrobial agents, defoamers, antioxidants, etc. Such additives may be introduced into the dispersion after the polymerization is completed.
[0086] The dispersion of the (meth)acrylate copolymer containing hydroxyalkyl (meth)acrylate comonomer units according to the present disclosure has a polymer solids content of 40% to 60% by weight. It should be understood that the dispersion can be diluted with water to any desired solids content depending on the specific application. The number average particle size (cumulative amount z-average) of the polymer particles dispersed in the dispersion is generally in the range of 50 to 1000 nm, preferably in the range of 50 to 750 nm, and most preferably in the range of 100 to 500 nm.
[0087] The weight average molecular weight Mw of the copolymer included in the dispersion according to the present disclosure is in the range of 10,000 to 1,000,000 g / mol, preferably 50,000 to 500,000 g / mol, most preferably 100,000 to 300,000 g / mol. The copolymer included in the dispersion according to the present disclosure has an Mw in the range of 1 to 10, preferably in the range of 1 to 5, most preferably in the range of 2 to 4. w / M n Compare.
[0088] The present invention further relates to the use of a dispersion of a (meth)acrylate copolymer containing hydroxyalkyl (meth)acrylate comonomer units according to the present invention for a flexible cementitious waterproofing material. The composition and preparation of the dispersion are as discussed in detail above.
[0089] There is no specific restriction on the cement contained in the cementitious material. Any known cement can be used, such as high-alumina cement and silicate cement. The silicate cement herein includes but is not limited to Portland cement, pozzolanic cement, hydraulic lime, fly ash and natural cement.
[0090] The cementitious material may also contain conventional additives known in the art. These additives include, but are not limited to, inorganic fillers such as calcium carbonate, quartz sand, dolomite, fumed silica, kaolin, talc and mica, rheology modifiers such as MW 40000, D and 3003F, superplasticizer such as 2651F, defoamer such as EL and NXZ, coalescence agent such as Plasticizers such as 3060, etc.
[0091] The dispersion of the (meth)acrylate copolymer according to the present disclosure is used in an amount of 10 to 100% by weight (in terms of solid content) relative to the weight of cement in the flexible cementitious waterproof material.
[0092] The dispersion of the (meth)acrylate copolymer containing hydroxyalkyl (meth)acrylate comonomer units according to the present invention can be mixed with other components such as cement, sand and optional additives, which together with the dispersion form a flexible cementitious waterproof material in situ just before application. The dispersion can be uniformly mixed with the flexible cementitious waterproof material by any mixing or blending means.
[0093] Additionally, the present invention provides a cementitious material containing a (meth) acrylate copolymer powder obtained from a dispersion of a (meth) acrylate copolymer containing a (meth) acrylate comonomer unit according to the present disclosure. For components that can be used for cementitious materials, in addition to the (meth) acrylate copolymer powder, reference may also be made to those described above.
[0094] It is understood that the (meth)acrylate copolymer powder obtained from the dispersion of the (meth)acrylate copolymer containing (meth)acrylate comonomer units according to the invention as described above is used in an amount of 10 to 100% by weight relative to the weight of cement in the cementitious material.
[0095] The invention is further described and illustrated in the examples, however the invention is not limited to the embodiments described in the examples.
[0096] Examples
[0097] In the context of the present invention, tensile strength and adhesive strength are measured according to GB / T 23445-2009, "Test Method of Building Waterproofing Coatings", 1st edition, June 2008. Ammonia release and aldehyde release from the dispersion are measured according to JC 1066-2008. The polymer solids content of the dispersion is determined according to ISO 3251:2008 by drying the dispersion in an oven at 140°C for 30 minutes.
[0098] The Tg of the copolymers of the present invention is measured by differential scanning calorimetry (DSC) taking the midpoint of the heat flow versus temperature transition as the Tg value. During the DSC test, the temperature is increased at 10°C per minute.
[0099] Disponil LDBS23IS: Surfactant, n-alkyl-(C 10 -C 13 ) Sodium alkylbenzene sulfonate, from BASF, Germany
[0100] Seed 6772: Pre-product 6772, polystyrene seed, from BASF
[0101] NaPS (sodium persulfate) solution, 7 wt.%, from ABC UNITED-INITIATORS HEFEI LIMITED COMPANY
[0102] Styrene (ST): from BASF
[0103] n-Butyl acrylate (BA): from BASF
[0104] Ethyl acrylate (EA): from BASF
[0105] 2-Ethylhexyl acrylate (EHA): from BASF
[0106] Methyl methacrylate (MMA): from BASF
[0107] N,N-bis(2-hydroxyethyl)methacrylamide (NN-MAM): from BASF
[0108] N-2-Hydroxyethyl-acrylamide (HEAA): from KJ Chemical
[0109] N-Methylol (meth) acrylamide (N-MAM): from KJC Chemicals
[0110] Example 1
[0111] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded in 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture containing 300g styrene (ST), 690g n-butyl acrylate (BA) and 10g N-2-hydroxyethyl-acrylamide (HEAA) was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0112] Example 2
[0113] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded in 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture comprising 200g styrene (ST), 300g ethyl acrylate (EA), 485g n-butyl acrylate (BA) and 15g N-2-hydroxyethyl-acrylamide (HEAA) was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0114] Example 3
[0115] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded in 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture comprising 200g styrene (ST), 495g ethyl acrylate (EA), 290g 2-ethylhexyl acrylate (EHA) and 15g N-2-hydroxyethyl-acrylamide (HEAA) was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0116] Example 4
[0117] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded in 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture comprising 270g styrene (ST), 100g ethyl acrylate (EA), 320g n-butyl acrylate (BA), 300g 2-ethylhexyl acrylate (EHA) and 10g N-2-hydroxyethyl-acrylamide (HEAA) was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0118] Example 5
[0119] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g of 7wt.% NaPS (sodium persulfate) solution was loaded within 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture containing 300g styrene (ST), 690g n-butyl acrylate (BA) and 10g N,N-bis(2-hydroxyethyl) methacrylamide (NN-MAM) was continuously fed over 5 hours. Then, 43g of NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0120] Example 6
[0121] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g of 7wt.% NaPS (sodium persulfate) solution was loaded within 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture containing 280g methyl methacrylate (MMA), 685g n-butyl acrylate (BA) and 15g N-2-hydroxyethyl-acrylamide (HEAA) was continuously fed over 5 hours. Next, 43g of NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0122] Comparative Example 1
[0123] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded within 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture containing 297g styrene (ST), 688g n-butyl acrylate (BA) and 15g acrylamide was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0124] Comparative Example 2
[0125] 500g DI water, 12g Disponil LDBS23IS and 10g of seed 6772 were loaded into a 5L automated reactor. The mixture was heated to 75°C. When the temperature was stable, 71g 7wt.% NaPS (sodium persulfate) solution was loaded within 2 minutes and stirred for another 3 minutes. When the temperature reached 75°C again, a monomer mixture containing 300g styrene (ST), 690g n-butyl acrylate (BA) and 15g N-hydroxymethyl (methyl) acrylamide (N-MAM) was continuously fed over 5 hours. Then, 43g NaPS 7wt.% solution was loaded, and the dispersion was post-polymerized for another 1 hour. Finally, the pH and solid content of the final product were adjusted to 7.2 and 50wt.%, respectively.
[0126] The composition and properties of the (meth)acrylate copolymer are listed in Table 1.
[0127] Table 1
[0128]
[0129]
[0130] *The detection value of aldehydes by HPLC instruments is 3ppm. If the aldehyde content is lower than 3ppm, the instrument cannot detect it.
Claims
1. A dispersion of a (meth)acrylate copolymer obtained by polymerization of monomers comprising: based on the total monomer weight, (a) 10 to 45% by weight of at least one monoethylenic hard monomer; (b) 54 to 89% by weight of at least one monoethylenically soft monomer (b); (c) 0.5 to 5.0% by weight of at least one monomer represented by formula (1) CH2=C(R 1 )CONR 2 R 3 Formula (1) Where R 1 represents a hydrogen atom or a methyl group, R 2 is a hydroxyalkyl group containing 2 to 8 carbon atoms, and R 3 is H, alkyl or hydroxyalkyl having 2 to 8 carbon atoms; and (d) 0 to 25% by weight of a monoethylenically unsaturated monomer containing at least one functional group selected from the group consisting of carboxyl, carboxylic anhydride, sulfonic acid, phosphoric acid and hydroxyl.
2. The dispersion according to claim 1, wherein The R 2 and R 3 is a hydroxyalkyl group containing 2 to 6 carbon atoms, R 3 is H, C1-C6 alkyl or hydroxyalkyl containing 2 to 6 carbon atoms; more preferably, R 2 is a hydroxyalkyl group containing 2 to 4 carbon atoms, and R 3 It is H, C1-C4 alkyl or hydroxyalkyl having 2 to 4 carbon atoms.
3. The dispersion according to claim 1, wherein The monomer (c) is selected from N-(2-hydroxyethyl)acrylamide, N,N-bis(2-hydroxyethyl)methacrylamide or a mixture thereof.
4. The dispersion according to any one of claims 1 to 3, wherein The at least one monoethylenic hard monomer (a) is selected from methyl methacrylate, tert-butyl acrylate, benzyl methacrylate, ethyl methacrylate, vinyl maleate, vinyl acetate, vinyl butyrate, vinyl formate, vinyl valerate, vinyl versatate, monovinyl aromatic monomers and any mixtures thereof.
5. The dispersion according to any one of claims 1 to 4, wherein The at least one monoethylenic soft monomer (b) may include, but is not limited to, methyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, nonyl acrylate, ethyl acrylate, decyl methacrylate, isodecyl methacrylate, hexyl (meth)acrylate, cyclohexyl acrylate, dodecyl (meth)acrylate, octyl methacrylate, propyl acrylate, ethylene adipate, diethyl fumarate, 1,4-butadiene, 1-pentene, di-2-ethylhexyl maleate, di-2-ethylhexyl fumarate, and mixtures thereof.
6. The dispersion according to any one of claims 1 to 5, wherein At least one monoethylenic hard monomer is used in an amount of 15 to 45%, preferably 20 to 40%, more preferably 20 to 30%, based on the total weight of all monomers.
7. The dispersion according to claim 6, wherein The at least one monoethylenically soft monomer (b) is used in an amount of 54 to 84%, preferably 59 to 79%, more preferably 69 to 79%, based on the total weight of all monomers.
8. The dispersion according to claim 7, wherein The monomer (c) is used in an amount of 0.5 to 4%, preferably 0.8 to 3%, more preferably 0.8 to 2.2%, most preferably 1 to 2%, based on the total weight of all monomers.
9. The dispersion according to claim 7, wherein The monomer (d) is used in an amount of 0.5 to 25%, preferably 1 to 15%, more preferably 0.8 to 2.2%, most preferably 1 to 2%, based on the total weight of all monomers.
10. The dispersion according to any one of claims 1 to 8, wherein The Tg of the copolymer is -30°C to 10°C, preferably -20°C to 10°C, more preferably -10°C to 0°C.
11. The dispersion according to any one of claims 1 to 8, wherein The Mw of the copolymer is 10,000 to 1,000,000 g / mol, preferably 50,000 to 500,000 g / mol, more preferably 100,000 to 300,000 g / mol.
12. Use of a dispersion of a (meth)acrylate copolymer according to any one of the preceding claims as a cementitious material.
Citation Information
Patent Citations
Elastic styrene acrylic emulsion for polymer cement waterproof coating and preparation method thereof
CN101891859A
Crosslinked acrylic emulsion for waterproofing paints and preparation method thereof
CN102911580A
Method of imparting salt and / or mechanical stability to aqueous polymer microsuspensions
US4269749A
A dispersion of (METH)acrylate copolymer containing a hydroxyalkyl (METH)acrylate functional monomer unit for flexible cementitious waterproofing materials
WO2016001256A1